RANCANG BANGUN SISTEM INFORMASI PENGAJUAN PENGADAAN SUKU CADANG MOBIL PADA PT. ANDALAN CHRISDECO BERBASIS WEB - Anwar, Syaiful; Irawan, Fahrizal (LPPM Universitas Nusa Mandiri, 2017)
In this era of globalization, information technology drove quickly. The computer and the Internet are tools created to facilitate the work of man. PT. Chrisdeco mainstay needs the existence of an information system that supports the work on the submission process of procurement of spare parts in order to work more efficiently and effectively. To which the author tries to make the final assignment submission of information systems procurement of spare parts in PT. Andalan Chrisdeco which until now has not been computerized. At this time PT. Chrisdeco mainstay is a company engaged in the sale and repair of automobiles. The existing system at PT. Chrisdeco mainstay has been computerized on almost any part of the submission process, but for the procurement of spare parts is still done manually, cannot be accessed through the Internet. This resulted in spare parts procurement process takes quite a long time due to the condition of an audit that is in charge of examining and approving the submission of procurement of spare parts that have high mobility, or in other words the person is seldom in the workspace since worked in several companies.